(untitled) (Eurasian Journal of Learning and Academic Teaching, 2023)
This paper reports about discussion of the differences between speech and writing. We reaffirmed the stand taken traditionally by linguists on the priority of speech over writing, but noted that the relation was a lot more complex than linguists had often acknowledged, and that in general it was highly misleading to present written language simply as a derivative of spoken language. The main problem in identifying differences between speech and writing is that this contrast interacts in complicated ways with other contrasts, so it is hard to find comparable written and spoken texts that do not differ in other respects as well. It is probably misleading to assume that speech is most typically spontaneous, private, etc., and that writing is most typically planned, public, etc., since other permutations of these contrasts are common. We noted a number of structural differences between certain written and spoken genres, but we were unable to decide clearly which of them were predictable consequences of the differences between speaking/hearing and writing/reading, and which of them were just conventional. We disputed the claim that speech is less explicit than writing, and a number of other widely held views - including some which are widely held by linguists. We agreed that the view of language which is espoused by many linguists is unduly influenced by the idea that written language is basic